Estudo do efeito de lesões seletivas no grupamento noradrenérgico A5 no reflexo auditivo de sobressalto e na inibição por estímulo prévio - Ferreira, Michelle de Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The cochlear root neurons are the first neurons of the central nervous system to receive auditory information from the cochlea and connect with sensorimotor integration centers of the brainstem, in particular the reticular pontine caudal nucleus. Functionally, the cochlear root neurons are involved in elementary circuit of the acoustic startle reflex, which is composed by the ganglion cells of the organ of Corti, the reticular pontine caudal nucleus and the motor neurons of the spinal cord. The acoustic startle reflex presents a series of modulations such as habituation, sensitization, prepulse inhibition and potentiation by an adverse stimulus. Changes in reflex reaction and in its different modulations have diagnostic value in the clinic of neurodegenerative and psychiatric diseases such as Parkinson's and schizophrenia. The modulations of the acoustic startle reflex occur by the influence overnuclei of the elementary circuit of this reflex. The nucleus least studied in the startle reflex neural circuit is the cochlear root nucleus. The pattern of efferent connectivity of the cochlear root neurons is well known but little is known about the origins of their afferent and the neurochemical identity of that. Previous studies have demonstrated that dendrites and soma of the neurons of the cochlear root synaptic buttons are covered by the four types suggesting that there are several sources for these axon terminals, with its own neurochemical characteristics. Recent experiments in our research group identified afferents to CRN from two important noradrenergic regions of the brainstem: the noradrenergic group A5 (A5) and the locus coeruleus (LC). However for the A5 grouping there are no behavioral studies on functional aspects of this connection. Furthermore, in order to determine the involvement of neuropeptide modulation of the RAS, there are reports in the literature on co-existence with the transcript of noradrenaline and neuropeptide regulated...

Os neurônios da raiz coclear são os primeiros neurônios do sistema nervoso central a receber a informação auditiva proveniente da cóclea e conectam-se com centros de integração sensoriomotora do tronco encefálico, especialmente com o núcleo reticular caudal da ponte. Funcionalmente os neurônios da raiz coclear estão envolvidos no circuito elementar do reflexo auditivo de sobressalto (RAS) juntamente com as células ganglionares do órgão de Corti, o núcleo reticular caudal da ponte e os motoneurônios da medula espinal. O RAS apresenta uma série de modulações como a habituação, a sensibilização, a inibição por estímulo prévio e a potenciação por um estímulo adverso. As alterações na reação reflexa de sobressalto em suas diferentes modulações possuem valor diagnóstico na clinica médica de enfermidades neurodegenerativas e psiquiátricas como Parkinson e esquizofrenia. As modulações do RAS ocorrem mediante a influência de diversos núcleos sobre os componentes do circuito elementar deste reflexo. O núcleo menos estudado do circuito neural do RAS é o núcleo da raiz coclear. O padrão de conectividade eferente dos neurônios da raiz coclear é bem conhecido porém pouco se conhece sobre as origens de suas aferências e a identidade neuroquímica das mesmas. Estudos prévios demonstraram que o soma e os dendritos dos neurônios da raiz coclear estão cobertos por botões sinápticos de quatro tipos sugerindo que existam diversas origens para estes terminais axônicos, com características neuroquímicas próprias. Experimentos recentes em nosso grupo de pesquisa identificaram aferências aos CRN provenientes de duas importantes regiões noradrenérgicas do tronco encefálico: a região do grupamento noradrenérgico A5 (A5) e o locus coeruleus(LC). Contudo para o grupamento A5 não existem estudos comportamentais a respeito de aspectos funcionais desta conexão. Além disso, buscando averiguar a participação...
Keywords: Norepinefrina; Neurorreguladores; Neuronios; Reflexo de sobressalto; Coclea; Tronco encefalico; Locus Cerúleo; Reflex, Startle; Locus coeruleus